A New Scale to Assess the Severity and Prognosis of Pulmonary Alveolar Proteinosis - JiuWu Bai; JinFu Xu; WenLan Yang; Beilan Gao; Weijun Cao; Shuo Liang; Huiping Li (Canadian Respiratory Journal)
Background. Pulmonary Alveolar Proteinosis (PAP) is a syndrome characterized by pulmonary surfactant accumulation. Small proportion of PAP patients experienced spontaneous remission. Objective. The aim of this study was to assess the severity and prognosis of PAP using various indexes. Methods. Characteristics, PaO2, lung function parameters, and HRCT score of 101 patients with PAP were retrospectively analyzed. Many indexes were explored and integrated into a scale. Results. PaO2 was lower among smokers than among never-smokers. PaO2 differed between each pair of patient groups stratified according to HRCT score or DLCO, % predicted, which differed between any two groups stratified according to PaO2. The PAP patients who died presented with more symptoms, a higher HRCT score, and lower DLCO, % predicted, than survivors. Smoking status, symptoms, PaO2, HRCT score, and DLCO, % predicted, were integrated into a scale (severity and prognosis score of PAP (SPSP)). SPSP correlated positively with PaO2, FVC, % predicted, FEV1, % predicted, and DLCO, % predicted, and negatively with HRCT score. The patients who died displayed a higher SPSP than survivors. Conclusion. Smoking status, symptoms, PaO2, HRCT score, and DLCO, % predicted, were integrated into a scale (SPSP) that can be used to assess the severity and prognosis of PAP to some degree.